SAFETY STANDARDS AFFECTING THE DECISION TO PARTICIPATE IN SPORTS EVENTS: A CASE STUDY OF MARATHONS IN THAILAND - Sirikulvadhana, Tanaphat; Boonpienpon, Nopparat; Weerapaiboon, Wongladda (Journal of MCU Nakhondhat, 2025)
This academic article aims to explain the conceptual framework related to safety standards that influence the decision to participate in sports events, with a case study on marathon events in Thailand. Currently, marathon events in Thailand have been gaining popularity, attracting many participants, including amateur and professional runners. At the same time, safety standards in marathon event organization remain a crucial issue that requires further development. This is especially true for current operational guidelines, which face the escalating challenge of PM 2.5 air pollution, making it a growing concern for marathon organizers. To elevate event organization to international standards such as those set by World Athletics and AIMS (Association of International Marathons and Distance Races), which are globally recognized certifying bodies, it is necessary to consider key factors affecting runner safety. These include racecourse management, medical support, emergency prevention measures, and crowd management. The researcher has established a conceptual framework for this study on sports tourism by reviewing relevant literature. The findings suggest that sports event management, safety management, and theories related to risk perception, perceived hygiene, health awareness, event safety atmosphere, participant confidence, and behavioral intention are essential aspects for research to enhance safety standards in sports event organization in Thailand.